Antigua and Barbuda : 2007 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Authorities of Antigua and Barbuda. (IMF Staff Country Reports; Country Report, 2008)
This 2007 Article IV Consultation highlights that macroeconomic outcomes for Antigua and Barbuda have strengthened significantly in recent years. Real GDP growth averaged 5 percent during 2003-05, and is estimated to have reached 12 percent in 2006. There has been progress in implementing broad structural reforms. On fiscal issues, the authorities intend to enhance revenue performance, including the introduction of a more flexible mechanism for retail fuel pricing in 2008. They also intend to improve the investment climate, reduce skill mismatches, exports, and deregulate telecommunications.